Pengaruh Kualitas Produk, Citra Merek, dan Promosi terhadap Keputusan Pembelian Mobil Toyota Sienta di Auto2000 Cabang HR Muhammad Surabaya - Debito Andri Kristanto; Hery Pudjoprastyono (UNHI Press, 2022)
This research was conducted at the Auto2000 dealer, HR Muhammad Surabaya branch, East Java. The purpose of this research is to determine the effect of product quality, brand image, and promotion on purchasing decisions. The total sample is 60 respondents, using the non-probability sampling method. Collecting data using a questionnaire with a sample of consumers who buy Toyota Sienta cars at the Auto2000 dealer HR Muhammad Surabaya branch. The analysis technique uses Partial Least Squares (PLS). In the study, it was found that product quality and brand image had a significant positive effect on purchasing decisions. Meanwhile, the promotion has no significant positive effect on purchasing decisions